Composição e ritmo circanual do leite em amostras de fazendas brasileiras - Rezende, João Pedro Andrade (2022)
The milk solids content is gaining importance in Brazil, as a criterion for defining milk prices and/or as a nutritional tool. Thus, the objectives of this work were: 1) to verify the temporal evolution in the contents of milk fat and crude protein (CP) in the country; 2) to quantify an annual rhythm in these same components and 3) to observe if problems in nutritional management can be detected with analysis of individual milk. In the objectives 1 and 2, two databases were analyzed. The first database, extracted from the Observatório de Qualidade do Leite, contained the monthly fat and CP contents of bulk tank milk from the six largest producing states in the country, from 2013 to 2020. The second database was obtained from Instituto Clínica do Leite and contained results of individual milk analysis from 261 farms, from 2017 to 2020, located mostly in Minas Gerais (MG) and São Paulo (SP). To achieve objective 1, annual least squares means (LSM) for fat content and CP of tank and individual milk were calculated and compared using the Tukey test (P ≤ 0.05). For tank milk data, there was an evolution only in the South region, where CP increased by an average of 0.07 percentage points, from 2017 to 2020. For individual milk data, in MG the fat contents (3.47 vs. 3.65%) and CP (3.33 vs. 3.40%) increased, while in SP only CP content (3.32 vs. 3.44%) increased. For objective 2, monthly LSM for fat and CP content were calculated and adjusted to a linear form of the cosine function every 12 months, applying the cosinor technique, often used in rhythm analyses. For all states, for bulk tank and individual milk, the cosinor fit was significant (P < 0.001) and better than the linear, quadratic or cubic fit for month of the year. The highest levels of milk fat occurred in May, with the average difference between the highest and lowest values observed throughout the year being 0.35 percentage units. The highest levels of CP occurred in May and June, with the average difference between the highest and lowest values observed throughout the year being 0.19 percentage units. These results demonstrate the existence of a circannual biological rhythm in the solid contents of milk produced in Brazil. To achieve objective 3, two pens of lactating cows, confined and fed a total mixed diet (TMR), were monitored for seven months. Every 18 days, individual milk production and composition; pen dry matter intake; TMR and leftovers samples; particle distribution evaluation, mixing quality and sorting using Penn State sieves and rumination score were collected. The observations per pen were divided into three groups, adopting fat or CP content as the division criterion. The LSM for all variables collected were generated, having group as fixed effect and pen as random effect in the statistical model, and compared using the Tukey test (P ≤ 0.05; trend P ≤ 0.10). Between groups by milk fat, differences were the proportion of particles from 8 to 19 mm and rumination score, while trends were observed for ether extract, physically effective neutral detergent insoluble fiber and selection against particles > 19 mm. Among groups by CP, the proportion of particles from 8 to 19 mm, sorting against particles >8 mm and in favor of particles from the bottom differed, in addition to a tendency for a coefficient of variation (CV) in the 8 mm sieve.